Larvicidal activity, molluscicide and toxicity of the essential oil of Citrus limon peels against, respectively, Aedes aegypti, Biomphalaria glabrata and Artemia salina - Barros Gomes, Paulo Roberto; Oliveira, Marlucy Bezerra; de Sousa, Dionney Andrade; da Silva, Jeremias Caetano; Fernandes, Romer Pessôa; Louzeiro, Hilton Costa; de Oliveira, Rayone Wesley Santos; de Paula, Maria do Livramento; Mouchrek Filho, Victor Elias; Fontenele, Maria Alves (Eclética Química, 2019)
In this present work, we tested the larvicidal activity, molluscicide and toxicity of the oil extracted from Citrus limon peels, respectively against third stage larvae of Aedes aegypti, snail Biomphalaria glabrata, and Artemia salina. For this, we extract the essential oil by hydrodistillation. Then, we identified and quantified the components by gas chromatography coupled to mass spectrometry (GC-MS). We tested the larvicidal and molluscicidal activity, respectively, using the method adopted by the Brazilian Ministry of Health and the World Health Organization. We calculated the lethal concentration (LC50) from the Probit method for the three biological activities with 95 %. The results of the chromatographic analysis showed that the oil has 58.81% of Limonene (major constituent) and 0.11% α-Mulene (minority component). The essential oil presented lethal concentration (LC50) for larvicidal activity, molluscicide and toxicity, respectively at 15.48, 13.05 and 743.35 mg∙L-1. Therefore, the essential oil is active against larvae of A. aegypti and snail B. glabrata and non-toxic against larvae of A. salina.